Frame of Act of “Infidelity in Love” and Its Euphemistic Representations in Russian and English Linguocultures - L. A. Bushuyeva (Научный диалог)
Euphemisms that act as means of linguistic representation of the act of “infidelity in love relationships” in the Russian and the English are examined in the article. The novelty of the research is seen in the fact that the situation of the act of “infidelity in love” is presented in the form of a frame model, in the structure of which slots are allocated that actualize various aspects of the situation under consideration. It is shown that in Russian linguoculture the slots “Agent of an act and its properties”, “Counterparty of an act”, “Patient of an act”, “Action as a manifestation of an act”, “Evaluation of an act, an agent of an act”, “Place of the act” are objectified. It was revealed that in the English linguistic culture, in addition to the indicated slots, the “Motive of Action” slot is also updated. Comparison of the semantics of the euphemistic units of the two languages showed that the euphemization of the act of “infidelity in love” is based on similar techniques: the mechanism of linguistic generalization, replacement of direct nomination with a foreign lexeme, pronominalization, meiosis, metonymic / metaphoric transfer. It is shown that the actualization of infidelity is carried out on the basis of similar metaphorical concepts MOVEMENT, RELATIONSHIP, ENTERTAINMENT / RECREATION, POLLUTION, which are identified both in Russian and in English, and the metaphorical concept of SPORT is found only in English.